2021
DOI: 10.3389/fimmu.2021.680506
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of the Measles Antibody Levels in Healthy Medical Personnel of Maternity Ward and Women in Labor

Abstract: It has been proven that post-vaccination immunity to measles virus after two doses of vaccine is not able to persistently protect against infection throughout life. The goal of this research was to determine the immune layer to the measles virus among women in labor and maternity ward personnel in the same medical institution. The levels of IgG antibodies to measles virus in the umbilical cord blood of 594 women in labor and 88 workers of the maternity ward were studied by ELISA. It was revealed that 22.7% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 20 publications
(25 reference statements)
1
6
0
Order By: Relevance
“…In our study of anti-measles immunity in patients with severe progressive bronchopulmonary disorders, the proportion of seronegative patients was 19%. This is comparable to the proportion of seronegative individuals in a healthy population [16,19,22]. According to foreign authors, the proportion of seronegative individuals among candidates for organ transplantation ranges between 1.4% and 13.2% [33][34][35][36].…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…In our study of anti-measles immunity in patients with severe progressive bronchopulmonary disorders, the proportion of seronegative patients was 19%. This is comparable to the proportion of seronegative individuals in a healthy population [16,19,22]. According to foreign authors, the proportion of seronegative individuals among candidates for organ transplantation ranges between 1.4% and 13.2% [33][34][35][36].…”
Section: Discussionmentioning
confidence: 58%
“…In spite of mass primary measles vaccination and subsequent booster vaccination in children, both immunocompromised and immunocompetent adult patients have no evidence of long-term protective vaccine-induced immunity [ 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. In a meta-analysis conducted by A.V.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different researchers prove that the Sars-Cov-2 genome is the result of the recombination between two beta-coronavirus genomes: Pangolin and Bat coronavirus [ 7 , 8 , 29 , 30 ]. Various in silico studies search for the effect of the vaccination, especially with pneumococcal vaccines, to protect against symptomatic cases of SARS-CoV-2 infection and death [ 31 36 ]. Our main objective was to find similar amino-acid sequences in the S protein of the Sars-Cov-2 genome and the investigated proteins sequences mentioned above using the recombination between bioinformatics and signal processing tools.…”
Section: Discussionmentioning
confidence: 99%
“…The Vector-Best IgG-measles test system (Russia) was used in a study [62] to investigate the level of immunity to the measles virus in women in labor and staff of maternity hospitals in one medical institution. It was shown that the studied contingent is a risk group for measles due to the high proportion of seronegative individuals among women of childbearing age (both maternity hospitals' personnel and women in labor).…”
Section: Production Of Monoclonal Antibodies and Immunodiagnostic Kits In Russiamentioning
confidence: 99%